Preparation and properties of Nanostructure Zinc Oxide Thin Films - Saeed, Nada M. (Iraqi Journal of Physics, 2009)
Zinc Oxide (ZnO) is probably the most typical II-VIsemiconductor, which exhibits a wide range of nanostructures. Inthis paper, polycrystalline ZnO thin films were prepared by chemicalspray pyrolysis technique, the films were deposited onto glasssubstrate at 400 °C by using aqueous zinc chloride as a spraysolution of molar concentration of 0.1 M/L.The crystallographic structure of the prepared film was analyzedusing X-ray diffraction; the result shows that the film waspolycrystalline, the grain size which was calculated at (002) was27.9 nm. The Hall measurement of the film studied from theelectrical measurements show that the film was n-type. The opticalproperties of the film were studied using measurements from VISUVspectrophotometer at wavelength range (300-1100) nm; theoptical characterization shows that the films have an averagetransmittance 55% in the VIS regions. The refractive index wascalculated as a function of the photon energy, also the calculatedoptical energy gap was 3.3 eV and 3.1 eV for direct and indirectallowed transition respectively.